Arbeit Macht Frei (in Erinnerung An) : a literatura de testemunho e a construção da memória do Holocausto - Müller, Patricia dos Santos (2021)
By addressing the theme Literature of Testimony and the Holocaust, the work seeks to emphasize the personal and historical memory of the genocide planned and carried out by Nazi Germans against Jews, and other groups considered inferior, which occurred between 1942 and 1945. During this period, known like World War II, Nazi forces perpetrated the European Jewish genocide. Since then, the media and the editorial market have addressed the event, including news, reports, articles and interviews, using the term Holocaust to describe this historical fact. Furthermore, historiographical theoretical bases emphasize the construction of conditions for the understanding of the German organization in its ideology and implementation of the so-called “Final Solution”. As an objective, the research seeks to identify and validate the characteristics of the Literature of Testimony, through the analysis of aspects of memory and history present in the narrative of the novels Sisters in Auschwitz, by Rena Kornreich Gelissen and Heather Dune Macadam (2015), and Os Hitler’s ovens, by Olga Lengyel (2018). Through the Literature of Testimony (a genre consisting of a narrative of a personal character), worked by the bibliographical inductive method, sources such as literary memoirs describe the period lived by Rena Kornreich, Danka Kornreich, Olga Lengyel and many other Jewish women as prisoners of the countryside of concentration and extermination Auschwitz-Birkenau, located in the interior of Poland. Therefore, it is necessary to consider that, in the scope of literary studies, the expression Literature of Testimony produces narratives derived from reports of victims of large-scale traumatic events, as a way of recreating, through memory, the physical space and the events in it. lived, based on the experiences of subjects, presenting testimonial reports, giving voice to the survivors. The novels under analysis focus on the narrative of traumatic events, determined by political, historical and social reverberations. In this sense, the analysis of the testimonies in the works awakens the reader to an awareness that leads to a social action contrary to anti-Semitism, born from the understanding of what the Second World War was like. In addition, memory and testimony produce the literary work of the event that is part of History, even if over the years and with the death of the survivors of the Shoah (a term used by the Jews to define the Holocaust) the last voices lose strength in the face of anti-Semitic rhetoric. In short, memory enables reflection so that such facts do not come back to be repeated by humanity.